Mannheimia haemolytica vaccine. - Saad, Mohd Zamri; Saad, Mohd Zambri (2006)

(untitled)
There is provided by this invention a novel vaccine for immunizing small ruminants against Mannheimia haemolytica infection; particularly Mannheimia haemolytica serotype A2 infection. The vaccine is composed of inactive culture of Mannheimia haemolytica serotype A2 in a dosage effective to immunize small ruminants against the bacteria, in combination with an excipient. The vaccine is formulated for intranasal administration into small ruminants. There is further provided by this invention a novel method for preparing a vaccine for immunizing small ruminants against Mannheimia haemolytica A2 infection composed of inactivated culture of Mannheimia haemolytica serotype A2. Further provided by this invention is a novel kit for comprising an inactivated culture of Mannheimia haemolytica A2 infection comprising an inactivated culture of Mannheimia haemolytica serotype A2 preparation and an intrasanal delivery device.